2016
DOI: 10.5005/jp-journals-10024-1833
|View full text |Cite
|
Sign up to set email alerts
|

Association between Tooth Loss and Degree of Temporomandibular Disorders: A Comparative Study

Abstract: The tooth loss is directly related to the signs and symptoms of TMD. The degree of TMD was significantly higher in edentulous patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Another interesting statistical finding from the study is that males have a higher risk (1.433 times) of having both their condyles affected compared to females and have a higher risk of bilateral tooth loss (1.635 times) compared to females. Malheiros AS et al have studied the incidence of temporomandibular disorder edentulous patients and found that the degree of tooth loss is directly related to the signs and symptoms of TMD [ 55 ]. The above study agrees with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting statistical finding from the study is that males have a higher risk (1.433 times) of having both their condyles affected compared to females and have a higher risk of bilateral tooth loss (1.635 times) compared to females. Malheiros AS et al have studied the incidence of temporomandibular disorder edentulous patients and found that the degree of tooth loss is directly related to the signs and symptoms of TMD [ 55 ]. The above study agrees with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…10 There are also records of a possible association of this condition with the presence of signs and symptoms of temporomandibular dysfunction. [11][12][13][14][15][16][17][18] Temporomandibular disorders (TMD) is a common complaint among patients attending dental clinic 19 and represents a set of musculoskeletal conditions affecting bone, fibrous, cartilaginous, and\or muscular structures involved in mandibular movements. It is characterized by the presence of one or more symptoms such as pain at pre-auricular region, face or temple, limiting movement, raising up joint noise, among others.…”
Section: Introductionmentioning
confidence: 99%
“… 10 There are also records of a possible association of this condition with the presence of signs and symptoms of temporomandibular dysfunction. 11 12 13 14 15 16 17 18 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the higher severity of TMD signs and symptoms in edentulous subjects 8,9 has already been proven and it is important to be considered, whereas the most prevalent edentulous population is aged 65-74 years 10 . Thus, this study aimed to evaluate patient characteristics and the diagnosis of orofacial pain through the Research Diagnostic Criteria/ Temporomandibular Disorders (RDC/TMD) and their association with the impact on OHRQoL in a private elderly community dwelling.…”
Section: Introductionmentioning
confidence: 99%